Legal Certainty in Determining The Amount of Duty Tax on Acquisition of Land and Building Rights (Bphtb) - Yanuaria, Tri; Polontoh, Herry M. (Pena Justisia: Media Komunikasi dan Kajian Hukum, 2024)
The research carried out in Jayapura City with the title "Legal Certainty in Determining the Amount of Tax on Acquisition of Land and Building Rights" (BPHTB) aims to provide legal certainty regarding the imposition of Tax on Acquisition of Land and Building Rights. (BPHTB) in determining the amount of BPHTB tax. The method used is normative law and empirical law in relation to land and building tax collection.In accordance with applicable laws and regulations, BPHTB levies in Jayapura City do not yet have complete legal certainty. Tax Object Acquisition Value (NPOP) transaction value is no longer used as a basis for determining BPHTB tax, in Jayapura City the basis for determining BPHTB is the interpretation made by the tax authorities based on market prices, location of land and buildings and building conditions. This happens because of society's tendency to try to get around it BPHTB financing. Taxpayers declare the transaction price in accordance with the NJOP if the market price or transaction value is greater than the Sales Value of the Tax Object (NJOP). Taxpayers will also try to avoid it if the Tax Object Acquisition Value (NPOP) is lower than the Tax Object Sales Value (NJOP). The obstacles faced in collecting BPHTB are legal factors, factors outside the law and taxpayer factors